História e doutrina da Assembleia de Deus no Brasil : um estudo de caso - Silveira, Mateus do Nascimento (2019)
The Pentecostalism is a Christian movement that begun in 1906 with emphasis on Sanctification, Prayer, Gifts of the Holy Spirit and the Return of Christ. This movement transformed the world through doctrines such as Baptism in the Holy Spirit with evidence in speaking in the language of the angels and the imminent Return of Christ. Despite being a movement of approximately one century, Pentecostalism could only arise because, during the progressive history of Christianity, there were theologians who, through a systematic biblical study, reinterpreted the scriptures by finding a new way of living. Thus, this dissertation demonstrates the doctrine of this belief in Brazil, through a case study of the largest Brazilian Protestant denomination – the Assemblies of God – and its interpretation of the Holy Scriptures.